2013
DOI: 10.4047/jap.2013.5.2.153
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and thermal properties of polyamide versus reinforced PMMA denture base materials

Abstract: PURPOSEThis in vitro study intended to investigate the mechanical and thermal characteristics of Valplast, and of polymethyl methacrylate denture base resin in which different esthetic fibers (E-glass, nylon 6 or nylon 6.6) were added.MATERIALS AND METHODSFive groups were formed: control (PMMA), PMMA-E glass, PMMA-nylon 6, PMMA-nylon 6.6 and Valplast resin. For the transverse strength test the specimens were prepared in accordance with ANSI/ADA specification No.12, and for the impact test ASTM D-256 standard w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
62
1
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(80 citation statements)
references
References 30 publications
7
62
1
10
Order By: Relevance
“…Moreover, this result is in compliance with a study made by Salman and Saleem 37 which revealed that denture cleansers decreased the flexural strength of nylon denture base materials. On the contrary to our study, Soygun et al 42 , found that polyamide based For both groups (flexible denture base resin and microwave cured denture resin groups); Corega Tabs recorded the statistically significant lowest flexural strength values (53.78±1.38,60.23±1.49 respectively). This was attributed to the fact that peroxide radical formed from alkaline peroxide denture cleanser might attack the polymer chain backbone causing polymer degradation producing decrease in strength 31 .…”
Section: There Was a Non-significant Direct Correlation Between Colorcontrasting
confidence: 99%
“…Moreover, this result is in compliance with a study made by Salman and Saleem 37 which revealed that denture cleansers decreased the flexural strength of nylon denture base materials. On the contrary to our study, Soygun et al 42 , found that polyamide based For both groups (flexible denture base resin and microwave cured denture resin groups); Corega Tabs recorded the statistically significant lowest flexural strength values (53.78±1.38,60.23±1.49 respectively). This was attributed to the fact that peroxide radical formed from alkaline peroxide denture cleanser might attack the polymer chain backbone causing polymer degradation producing decrease in strength 31 .…”
Section: There Was a Non-significant Direct Correlation Between Colorcontrasting
confidence: 99%
“…1b and 1c) showed agreement that long-term exposure to the oral cavity can lead to a decrease in hardness of the surface. On the other hand, occlusal force and thermal changes due to food and drink can be transmitted to the dentures (>100 µm) 5,7,8) , supporting that the decrease in hardness is caused not only by physiochemical factors but also by biological factors such as salivary enzymes and/or oral microbiota.…”
Section: Hardness Testmentioning
confidence: 98%
“…This deterioration is likely to be not only due to physiochemical factors such as heat and mechanical loading, but also to biological factors such as salivary enzymes and bacterial metabolic activity 2) . There are many studies about the physiochemical deterioration of surface properties and bending strength of PMMA due to water absorption 3) , chemical reagents such as ethanol and acid 4) , mechanical stress such as occlusal force 5) and thermal stress such as dietary components [6][7][8] . On the other hand, the elution of monomers from PMMA prosthesis 9,10) is the only study topic concerned with biological factors, such as salivary enzymes and oral microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…[1] When compared with PMMA, valplast (the most commonly used thermoplastic nylon) has higher transverse strength (117.22 ± 37.80 MPa) as well as impact strength (0.76 ± 0.03 kN). [2] III.…”
Section: Materials and Its Propertiesmentioning
confidence: 99%
“…The elastic modulus of flexible nylon (valplast) is lesser than that of PMMA. [2] The valplast shows clinically significant chromatic instability, so the flexible removable partial denture might show staining and discoloration with time. [9] As flexible dentures flex under occlusal load so these can notmaintain the vertical dimension.…”
Section: Disadvantagesmentioning
confidence: 99%